Endocannabinoid Signaling for GABAergic-Microglia (Mis)Communication in the Brain Aging - Carrera, Jorge; Tomberlin, Jensen; Kurtz, John; Karakaya, Eda; Bostanciklioglu, Mehmet; Albayram, Onder (Frontiers in Neuroscience, 2021)
The aging brain seems to be characterized by neuronal loss leading to cognitive decline and progressively worsening symptoms related to neurodegeneration. Also, pro-inflammatory states, if prolonged, may increase neuronal vulnerability via excessive activation of microglia and their pro-inflammatory by-products, which is seen as individuals increase in age. Consequently, microglial activity is tightly regulated by neuron-microglia communications. The endocannabinoid system (ECS) is emerging as a regulator of microglia and the neuronal-microglia communication system. Recently, it has been demonstrated that cannabinoid 1(CB1) receptor signaling on GABAergic interneurons plays a crucial role in regulating microglial activity. Interestingly, if endocannabinoid signaling on GABAergic neurons are disturbed, the phenotypes mimic central nervous system insult models by activating microglia and leading to accelerated brain aging. Investigating the endocannabinoid receptors, ligands, and genetic deletions yields the potential to understand the communication system and mechanism by which the ECS regulates glial cells and aspects of aging. While there remains much to discover with the ECS, the information gathered and identified already could lead to the development of cell-specific therapeutic interventions that help in reducing the effects of age-related pro-inflammatory states and neurodegeneration.